The Effects of Economic Growth, Financial Development, Trade Openness, and Energy Consumption on CO2 Emission in Indonesia - Sharly Jihannisa Nur Sahara; Hadi Rahadian (Jurnal Ekonomi Pembangunan, 2023)
This study investigates the effects of economic growth, financial development, trade openness, and energy consumption in Indonesia from 1980 to 2020. The analytical method used is autoregressive distributed lagged (ARDL) modeling. The data for the study is sourced from official websites such as the World Bank, Our World in Data, and British Petroleum. The study findings show that economic growth and energy consumption increase CO2 emissions in Indonesia in both the short and long run. On the other hand, financial development and trade openness significantly reduce CO2 emissions in Indonesia in the long run. In the short run, trade openness also helps decrease CO2 emissions in Indonesia. However, the financial development variable does not significantly impact CO2 emissions in Indonesia in the short run.